2019
DOI: 10.1093/eurheartj/ehz327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infective endocarditis in patients with positive blood cultures: a Danish nationwide study

Abstract: Aims Increasing attention has been given to the risk of infective endocarditis (IE) in patients with certain blood stream infections (BSIs). Previous studies have been conducted on selected patient cohorts, yet unselected data are sparse. We aimed to investigate the prevalence of IE in BSIs with bacteria typically associated with IE. Methods and results By crosslinking nationwide registries from 2010 to 2017, we identified pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 32 publications
0
23
2
Order By: Relevance
“…In order to avoid unnecessary investigations, recent work has focused on identifying risk factors of IE in EFsB. These studies have collectively demonstrated a relatively high risk for IE in patients with monomicrobial EFsB [15][16][17] and have suggested unknown focus of primary infection and several positive blood cultures as risk factors for IE in enterococcal bacteremia [17][18][19]. Thirty-day mortality in EFsB is around 20% and higher in patients with an abdominal focus of infection and nosocomial infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid unnecessary investigations, recent work has focused on identifying risk factors of IE in EFsB. These studies have collectively demonstrated a relatively high risk for IE in patients with monomicrobial EFsB [15][16][17] and have suggested unknown focus of primary infection and several positive blood cultures as risk factors for IE in enterococcal bacteremia [17][18][19]. Thirty-day mortality in EFsB is around 20% and higher in patients with an abdominal focus of infection and nosocomial infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococci at present are the most frequent etiologic organism. A Danish study showed that between 1957 and 1990, Staphylococcus aureus bacteremia increased from 3 to 20 per 100,000 person-years, paralleling the increase of hospital admissions and invasive medical procedures [7] . Hand-hygiene, barrier precautions, and antisepsis are effective measures in reducing the rate of bacteremia.…”
Section: Epidemiology Of Native Valve Endocarditismentioning
confidence: 99%
“…Infective endocarditis (IE) is associated with high morbidity and mortality caused by mainly gram positive cocci [4] , [5] , [6] , [7] , [8] . Recent studies have reported an increasing incidence of IE during the past two decades [9] , [10] , [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%